2013
DOI: 10.1016/j.smallrumres.2012.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative trait loci associated with pre-weaning growth in South African Angora goats

Abstract: This study aimed to identify chromosomal regions associated with genetic variation in preweaning growth traits in Angora goats. A genome-wide scan was performed by genotyping 1042 offspring from 12 half-sib families using 88 microsatellite caprine markers covering 1368cM.Phenotypes were recorded at birth (BW) and weaning (WW) and analysed using GridQTL software.A total of six putative QTL were detected on six different chromosomes, all at chromosome-wide significance level. Four QTL were identified for BW on C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…In a separate QTL identification study focusing on pre-weaning growth traits, four chromosomal regions of interest with an influence on birth weight (BW) were identified on CHI 4, 8, 18 and 27 (Visser et al, 2013). Analyses indicated two candidate regions for weaning weight (WW)…”
Section: Selectionmentioning
confidence: 99%
“…In a separate QTL identification study focusing on pre-weaning growth traits, four chromosomal regions of interest with an influence on birth weight (BW) were identified on CHI 4, 8, 18 and 27 (Visser et al, 2013). Analyses indicated two candidate regions for weaning weight (WW)…”
Section: Selectionmentioning
confidence: 99%
“…Quantitative trait loci for traits such as birth and weaning weight (Mohammad Abadi et al, 2009;Visser et al, 2013), hair fiber characteristics (Cano et al, 2007;Visser et al, 2011), growth (Mohammad Abadi et al, 2009), body conformation (Marrube et al, 2007), parasite resistance (Bolormaa et al, 2010;De La Chevrotière et al, 2012), milk traits (Roldán et al, 2008), and α S1 -casein (Sacchi et al, 2005;Hayes et al, 2006;Dagnachew et al, 2011) have been identified in goats using microsatellite markers. With the availability of the Illumina Caprine 50K BeadChip (Illumina Inc., San Diego, CA;Tosser-Klopp et al, 2012, 2014, it is now possible to perform genome-wide scans in goats Genome-wide association study of conformation and milk yield in mixed-breed dairy goats with much greater resolution.…”
Section: Introductionmentioning
confidence: 99%
“…) and CHI 4 and 18 in Angora goats (Visser et al . ), were associated with birth weight in other independent studies in goat, whereas QTL associated with birth weight in sheep were detected on CHI 14 (OAR 14; corresponding to CHI 18) in Scottish Blackface sheep (Hadjipavlou & Bishop ) and on OAR 3 (corresponding to CHI 5 and 1) in Merino sheep (Roldan et al . ).…”
Section: Discussionmentioning
confidence: 92%
“…In addition, QTL affecting birth weight on CHI 4 (68 cM), CHI 8 (0 cM), CHI 18 (17 cM) and CHI 27 (6 cM) and QTL for weaning weight on CH16 (68 cM) and CHI 19 (46 cM) have been recently reported by Visser et al . () in South African Angora goats but still need to be validated in other goat breeds. Thus, one of the objectives of this study was to map QTL affecting birth weight in Rayini cashmere goats.…”
Section: Introductionmentioning
confidence: 99%